Budaya Agama Dan Relasi Budaya Sedekah Laut Di Pesisir Kota Pati - Sakdiyah, Lailatus; Prateksa, Ardhanareswari; Dzikri Fillah, Jazidan; Chika Putri, Juwita Aulia; Indahsari, Reni Indahsari (Universitas Nahdlatul Ulama Sunan Giri, 2023)
Indonesia is a country with an abundance of cultures and traditions. One of the traditions that is still maintained, preserved and also practiced in the coastal city of Pati, Central Java Province is sedekah laut. Sedekah laut is a tradition that is carried out once a year on the first day of the Javanese calendar, the month of Suro. The type of research used in this study is a qualitative description method that focuses on the description and understanding of a phenomenon. The data used comes from journals, papers, and various other literature. This research aims to explain the tradition of sea alms on the coast of Pati City and analyze the values contained in the sea alms tradition. The sea alms tradition is carried out by the coastal communities of Pati City as a form of gratitude for the abundance of favors and sustenance both on earth and in the sea to God. This tradition acculturates local and Islamic cultures that can foster community harmony. Some of the values contained in the sea alms include the value of friendship, aqidah, worship, and alms. The functions of sea alms include entertainment, communication, cultural preservation, education and economy. The benefits of sea alms include the benefit of the community to share and help each other among the people who participate in the tradition.